Mirroring Integrity: Deconstructing The Role of Teachers as Moral Architects in Social Learning Ecosystems - Yuwita Rianawati; Siti Irene Astuti Dwiningrum (Assyfa Learning Journal, 2026)
Student character development faces ongoing challenges, such as low discipline, diminishing academic responsibility, and increasing exposure to negative social and digital media influences. This study aims to analyze the influence of Albert Bandura’s Social Learning Theory on students’ character formation and explain its practical relevance to character education within school environments. Utilizing a library research design with a descriptive qualitative approach, data were gathered from books, scientific journals, and scholarly publications, followed by qualitative content analysis. The findings demonstrate that character development operates through observational learning, modeling, reinforcement, and self-regulation, driven by reciprocal interaction among personal, behavioral, and environmental factors. Specifically, observational learning progresses through attention, retention, reproduction, and motivation, emphasizing that teachers, positive school cultures, and digital media figures serve as primary behavioral models. In conclusion, Bandura’s theory offers a comprehensive theoretical framework for modern character education, highlighting that teacher role modeling, habituation programs, and the cultivation of student self-regulation are essential for fostering sustainable moral integrity across physical and digital social learning ecosystems.